2007
DOI: 10.1002/bip.20714
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear magnetic relaxation dispersion study of the dynamics in solid homopolypeptides

Abstract: The (1)H nuclear magnetic relaxation dispersion profiles were measured from 10 kHz to 30 MHz as a function of temperature for polyglycine, polyalanine, polyvaline, and polyphenylalanine to examine the contributions of different side chain motions to the polypeptide proton relaxation rate constants. The spin-fracton theory for (1)H relaxation is modified to account for high frequency motions of side chains that are dynamically connected to the linear polymer backbone. The (1)H relaxation is dominated by propaga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…The difference is in the high field portion of the relaxation dispersion profile, which at low temperatures, preserving the power law, is displaced to higher relaxation rates relative to the extrapolation of the low field profile. This phenomenon was previously described in [21; 22], where it is shown that the increase in the relaxation rates is due to fast motion of covalently bound protein side-chain groups. Motion of phenyl rings was observed at low frequencies and elevated temperatures for polyphenylalanine while motions of methyl groups dominate at high frequency and low temperatures [22].…”
Section: Resultssupporting
confidence: 53%
See 4 more Smart Citations
“…The difference is in the high field portion of the relaxation dispersion profile, which at low temperatures, preserving the power law, is displaced to higher relaxation rates relative to the extrapolation of the low field profile. This phenomenon was previously described in [21; 22], where it is shown that the increase in the relaxation rates is due to fast motion of covalently bound protein side-chain groups. Motion of phenyl rings was observed at low frequencies and elevated temperatures for polyphenylalanine while motions of methyl groups dominate at high frequency and low temperatures [22].…”
Section: Resultssupporting
confidence: 53%
“…This phenomenon was previously described in [21; 22], where it is shown that the increase in the relaxation rates is due to fast motion of covalently bound protein side-chain groups. Motion of phenyl rings was observed at low frequencies and elevated temperatures for polyphenylalanine while motions of methyl groups dominate at high frequency and low temperatures [22]. Even though the motion of side-chain methyl groups is present at all temperatures, it is sufficiently slow only below 180 K for dry BSA to enter the observation window and offset the relaxation rate constant to larger values at the highest frequencies as shown in Fig.…”
Section: Resultssupporting
confidence: 53%
See 3 more Smart Citations